2019
DOI: 10.2147/ijn.s192219
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pulmonary delivery of transferrin receptors targeting peptide surface-functionalized liposomes augments the chemotherapeutic effect of quercetin in lung cancer therapy</p>

Abstract: Purpose: Lung cancer has a high incidence rate worldwide with a 5-year survival rate of 18%, and is the leading cause of cancer-related deaths. The aim of this study is to augment therapeutic efficacy of quercetin (QR) for lung cancer therapy by targeting transferrin receptors, which are overexpressed and confined to tumor cells. Methods: In this study, T7 surface-functionalized liposomes loaded with QR (T7-QR-lip) having different T7 peptide densities (0.5%, 1% and 2%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…The study indicated that a 2% peptide density for T7-QR-lip resulted in a significant inhibition in lung tumor spheroids growth. Inhibition of tumor growth and prolongation of lifespan after T7-QR-lip treatment through pulmonary administration was also confirmed with in vivo studies [140].…”
Section: Liposomessupporting
confidence: 54%
“…The study indicated that a 2% peptide density for T7-QR-lip resulted in a significant inhibition in lung tumor spheroids growth. Inhibition of tumor growth and prolongation of lifespan after T7-QR-lip treatment through pulmonary administration was also confirmed with in vivo studies [140].…”
Section: Liposomessupporting
confidence: 54%
“…Lung cancer, predominantly non-small-cell lung cancer (NSCLC), is one of the most common types of malignant cancer and the primary cause of tumor-associated mortality and morbidity worldwide with a high incidence rate and a 5-year survival rate of 18% (1). Platinum-based chemotherapy regimens are currently the standard adjuvant treatment strategy for advanced NSCLC following surgical resection (2).…”
Section: Introductionmentioning
confidence: 99%
“…These liposomes were evaluated for cellular uptake and in vitro cytotoxicity study and they exhibited higher cytotoxicity and S-phase cell cycle arrest. The in vivo study showed enhanced liposomes accumulation in the lungs and sustained release up to 96 h [184].…”
Section: Organic Nanoparticlesmentioning
confidence: 90%